APLIKASI TIKTOK SEBAGAI LITERASI MEDIA : ANAK MUDA ANTI NARKOBA - Siti Nurul Fadillah; Arifah M.A (MEDIOVA: Journal of Islamic Media Studies, 2022)
Drugs, a word that is already familiar to our ears, is still a complicated problem in Indonesia. Until now, Indonesia is still a country that is busy with the problem of eradicating, overcoming drugs. Based on data from the National Narcotics Agency (BNN) in Indonesia, in 2021 drug users will be 0.15 percent to 1.95 percent or around 3.66 million people. Drug abuse is not only experienced by young people but almost all levels of society, both officials and even artists. Drug addiction as a result of continuous consumption will have a negative impact both physically, psychologically, economically, socio-culturally and other impacts. Therefore, through this paper the author seeks to campaign for preventive measures from the bad influence of drugs through media literacy by utilizing the tiktok application. That by using the tiktok application, young people can go viral how dangerous drugs are by making short videos that are unique and interesting. This study uses a literature study that will collaborate with various literatures in the form of books, magazines, journals, and relevant literature.